2021
DOI: 10.3389/fneur.2021.722762
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement on High-Intensity Focused Ultrasound for Functional Neurosurgery in Switzerland

Abstract: Background: Magnetic resonance-guided high-intensity focused ultrasound (MRgHiFUS) has evolved into a viable ablative treatment option for functional neurosurgery. However, it is not clear yet, how this new technology should be integrated into current and established clinical practice and a consensus should be found about recommended indications, stereotactic targets, patient selection, and outcome measurements.Objective: To sum up and unify current knowledge and clinical experience of Swiss neurological and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For MRgFUS, the patient's tolerability of the MRI environment and the presence of MRI-incompatible implants must be considered (33). Additionally, the acoustic properties of the patient's skull must be understood (53). For all ablative procedures, the nonreversible and nonadjustable nature of the technique must also be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For MRgFUS, the patient's tolerability of the MRI environment and the presence of MRI-incompatible implants must be considered (33). Additionally, the acoustic properties of the patient's skull must be understood (53). For all ablative procedures, the nonreversible and nonadjustable nature of the technique must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is recommended that patients have a skull density ratio of >0.4 to be considered candidates for this treatment. Patients with artifacts from previous cranial surgical interventions or skull shape deformations may not be suitable candidates for MRgFUS ablation (53). Other considerations are that the patient's head must be shaved, and the MRI environment and increased operative time may be uncomfortable or intolerable for claustrophobic patients.…”
Section: Patient Considerations For Mrgfusmentioning
confidence: 99%
“…Axial symptoms, however, are far more challenging to treat because they usually do not respond to unilateral stimulation or ablation. Treatment chances and risks must be weighed carefully against each other, but long‐time experience from bilateral DBS in the GPi suggests that the profile of expected side effects should be acceptable 6 . Gallay et al 7 reported a series of 52 unilateral pallidothalamic tract (PTT)‐ablations in 2020 with good effectiveness on dyskinesias and favorable risk‐profile, and there is one ongoing open‐label study by Insightec about bilateral PTT ablation for the treatment of PD (NCT04728295).…”
Section: Discussionmentioning
confidence: 99%
“…Initial experience regarding staged bilateral FUS thalamotomy, particularly in patients with essential tremor, has been published. However, bilateral treatments are still considered experimental [ 134 ] and PD patients may not be good candidates for bilateral FUS for their intrinsic high risk of balance and gait problems.…”
Section: Surgical and Ablative Approaches To Pd Tremormentioning
confidence: 99%